2012
DOI: 10.1371/journal.pone.0032558
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Strand Interfaces of Non-Dimeric Protein Oligomers Are Characterized by Scattered Charged Residue Patterns

Abstract: Protein oligomers are formed either permanently, transiently or even by default. The protein chains are associated through intermolecular interactions constituting the protein interface. The protein interfaces of 40 soluble protein oligomers of stœchiometries above two are investigated using a quantitative and qualitative methodology, which analyzes the x-ray structures of the protein oligomers and considers their interfaces as interaction networks. The protein oligomers of the dataset share the same geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…We have shown that this distinction is necessary to exhibit features of intermolecular β-strands [32]. This is certainly related to the involvement of the backbone interactions in the hydrogen bond network of the β-sheets while in α-helices such backbone interactions are involved intramolecularly and are not interfering with intermolecular interactions.…”
Section: Resultsmentioning
confidence: 86%
“…We have shown that this distinction is necessary to exhibit features of intermolecular β-strands [32]. This is certainly related to the involvement of the backbone interactions in the hydrogen bond network of the β-sheets while in α-helices such backbone interactions are involved intramolecularly and are not interfering with intermolecular interactions.…”
Section: Resultsmentioning
confidence: 86%
“…Statistical analyses have been performed on the case of the β interfaces, that are formed by two adjacent β strands, one from each subunit [6][7][8]. In [8] the analysis has been extended to a dataset of 755 proteins.…”
Section: Basic Information On Interfacesmentioning
confidence: 99%
“…In other words, the backbone hydrogen bonds satisfy the mathematical property of symmetrically minimized distances and the backbone non-hydrogen atoms that engage in BB hydrogen bonds are reciprocal nearest neighbours, with the indicated accuracy. This identification has been obtained using the web server RING (see Methods) to calculate the hydrogen bonds and compare with the graphs (see also [6]). Among the 120 pairs of residues in the graphs (anti-parallel and parallel cases only), 108 are recognized by RING as hydrogen bonds and 12 are not.…”
Section: Basic Information On Interfacesmentioning
confidence: 99%
See 2 more Smart Citations